The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acs.nanolett.3c02351
|View full text |Cite
|
Sign up to set email alerts
|

Role of Defects in the Breakdown Phenomenon of Al1–xScxN: From Ferroelectric to Filamentary Resistive Switching

Roberto Guido,
Thomas Mikolajick,
Uwe Schroeder
et al.

Abstract: Aluminum scandium nitride (Al1–x Sc x N), with its large remanent polarization, is an attractive material for high-density ferroelectric random-access memories. However, the cycling endurance of Al1–x Sc x N ferroelectric capacitors is far below what can be achieved in other ferroelectric materials. Understanding the nature and dynamics of the breakdown mechanism is of the utmost importance for improving memory reliability. The breakdown phenomenon in ferroelectric Al1–x Sc x N is proposed to be an impulse the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Thus, both defect distribution and interface phenomena are suspected to play a decisive role in defining the energy required for ferroelectric switching in wurtzite-type systems. [26,37,43,44] By comparing the electric field magnitude at which the pristine to M-polar and subsequent N-to M-polar switching are achieved in Figure 3, it can be observed that the full N-to M-polar state reversal is attained with ≈0.3 MV cm −1 smaller electric field magnitude in the second switching transition. The decrease of the energy barrier for polarization reversal between the N-and M-polar states raises significant reliability concerns for both non-volatile memory applications and precise weight update in neuromorphic computing architectures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, both defect distribution and interface phenomena are suspected to play a decisive role in defining the energy required for ferroelectric switching in wurtzite-type systems. [26,37,43,44] By comparing the electric field magnitude at which the pristine to M-polar and subsequent N-to M-polar switching are achieved in Figure 3, it can be observed that the full N-to M-polar state reversal is attained with ≈0.3 MV cm −1 smaller electric field magnitude in the second switching transition. The decrease of the energy barrier for polarization reversal between the N-and M-polar states raises significant reliability concerns for both non-volatile memory applications and precise weight update in neuromorphic computing architectures.…”
Section: Resultsmentioning
confidence: 99%
“…[26] The continuously faster N-to M-polar switching could be explained by the alteration of the local electric field profile due to defect generation and redistribution. [26] The defect distribution could also influence the number of nucleation sites and density of domain walls, which are considered responsible for the origin of wakeup phenomenon in aluminum boron nitride (Al 1−x B x N). [23,40,41] In agreement with this hypothesis, Figure 3 shows that the first M-polar domains nucleate at different regions between the two consecutive N-to M-polar switching transitions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16) Various topics concerning Al 1−x Sc x N thin film have been actively investigated. For instance, sputter deposition, 17,18) epitaxial growth, 19,20) thickness scaling, [21][22][23][24][25][26] low-voltage operation, 27,28) thermal stability, 16,29) field cycling, 30,31) breakdown mechanism, 32) diode memory, 33) ferroelectric FET (FeFET), 34) etc. Low-temperature deposition by Al 1−x Sc x N sputtering down to RT was also reported, which reveals its compatibility with microelectronic integration.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Moreover, the inherent ferroelectricity of ScAlN is useful in fabricating nitride semiconductor-based ferroelectric field-effect transistors (FeFETs). [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Despite its significant potential, ScAlN remains a relatively new material with various unresolved questions regarding the interplay between its structural attributes, such as crystal structure, lattice constants, and physical properties. Notably, ScAlN predominantly crystallizes into a wurtzite structure at lower Sc compositions, and a Sc composition of 18% results in a lattice constant that matches that of GaN.…”
mentioning
confidence: 99%